Rest period requirements and role for Stylosanthes cereal cropping systems in the Nigerian subhumid zone - Mohamed-Saleem, M.A.; Adeoye, K.B.; Kaufmann, Ralph R. von (French Grassland Society, 1989)
Discusses the rest period requirements and the role of stylosanthes in cereal cropping systems in the Nigerian subhumid zone. Presents results of two trials, viz, N application on maize grain yield after natural fallow, and changes in soil physical properties after diffrent land use.